New Substrates and Enzyme Assays for the Detection of Mucopolysaccharidosis III (Sanfilippo Syndrome) Types A, B, C and D by Tandem Mass Spectrometry - Wolfe, Brian J. (2012)
The clinical phenotype of Sanfilippo Syndrome is caused by one of four enzyme deficiencies that are associated with a defect in mucopolysaccharide metabolism. The four subtypes (A, B, C, and D) are each caused by an enzyme deficiency involved in the degradation of heparan sulfate. We have developed a highly efficient synthesis of the substrates and internal standards required for the enzymatic assay of each of the four enzymes. The synthesis of the substrates involves chemical modification of a common intermediate. The substrates and internal standards allow the measurement of the enzymes relevant to heparan N-sulfatase (type A); N-acetyl-α-glucosaminidase (type B); acetyl-CoA:α-glucosamide N-acetyltransferase (type C); N-acetylglucosamine 6-sulfatase (type D). The internal standards are similar to the substrates and allow for the accurate quantitation of the enzyme assays using tandem mass spectrometry. The synthetic substrates incorporate a coumarin moiety and can also be used in fluorometric enzyme assays. We confirm that all four substrates can detect the appropriate Sanfilippo syndrome in fibroblast lysates, and the measured enzyme activities are distinctly lower by a factor of 10 when compared to fibroblast lysates from unaffected persons.